2002
DOI: 10.1097/00005537-200210000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Parathyroid Hormone Levels in Thyroid and Parathyroid Surgery

Abstract: The study demonstrates that intraoperative PTH levels greater than 15 pg/mL after total or completion thyroidectomy indicate a low risk of postoperative hypocalcemia and that these patients may be candidates for outpatient surgery. In the parathyroid group, intraoperative PTH levels do not correlate well with postoperative calcium levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 10 publications
4
64
2
2
Order By: Relevance
“…If patients undergoing total thyroidectomy fulfill neither of these criteria, close calcium monitoring and early supplementation of calcium/vitamin D may be needed for postoperative patients. The cutoff values to determine which patients will be safely discharged early or will need close monitoring and replacement therapy can show some differences between our study and prior reports: absolute ioPTH values at 10 pg/ mL 7,13 or 15 pg/mL 15 ; the decline percentage of ioPTH levels at 75%. 6,9 However, no previous studies have suggested such an algorithm with the combination of absolute values and decline percentage of ioPTH levels.…”
contrasting
confidence: 79%
See 2 more Smart Citations
“…If patients undergoing total thyroidectomy fulfill neither of these criteria, close calcium monitoring and early supplementation of calcium/vitamin D may be needed for postoperative patients. The cutoff values to determine which patients will be safely discharged early or will need close monitoring and replacement therapy can show some differences between our study and prior reports: absolute ioPTH values at 10 pg/ mL 7,13 or 15 pg/mL 15 ; the decline percentage of ioPTH levels at 75%. 6,9 However, no previous studies have suggested such an algorithm with the combination of absolute values and decline percentage of ioPTH levels.…”
contrasting
confidence: 79%
“…It has also been suggested that the rapid PTH assay might have a value in monitoring the outcome of thyroid surgery with respect to the development of postoperative hypocalcemia. 6,9,14,15 The reports asserted that the rapid PTH assay can identify patients at risk of clinically significant hypocalcemia earlier than achieved with serum calcium monitoring after thyroidectomy. In addition, intraoperative PTH levels greater than the cutoff values indicate a low risk of postoperative hypocalcemia and propose safe, early discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanying process, for instance vitamin D insufficiency, calcitonin realizes, "hungry bone syndrome" definitely conduce to this state (2,4). Authors have analyzed simple, reliable and sensitive instruments that may predict postoperative hypocalcemia (2,(5)(6)(7)(8)(9)(10). Serial measures of parathyroid hormone (PTH)…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as ionized calcium (iCa) levels that remain under 1.0 mmol/L or the development of clinical symptoms and signs (2). Hypocalcemia often increases the duration of hospital stay, overall cost of a thyroidectomy, need for frequent biochemical tests, and frequency of emergency room visit (3).…”
Section: Introductionmentioning
confidence: 99%